(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Groundwater plays a vital role in meeting the domestic, agricultural, and industrial water demands in the Anantnag district of Kashmir. However, the rapid urbanization, industrialization, and agricultural practices have raised concerns regarding the quality of groundwater in the region. This study aims to assess the groundwater quality in Anantnag, Kashmir, by evaluating key physicochemical parameters and determining the presence of potential contaminants. To achieve the objectives, a systematic sampling campaign was conducted across various locations in Anantnag district. Groundwater samples were collected from representative wells, tube wells, and hand pumps. A comprehensive analysis was carried out to determine the physicochemical parameters including pH, electrical conductivity (EC), total dissolved solids (TDS), and concentrations of major ions such as chloride (Cl-), nitrate (NO3-), sulfate (SO42-), and fluoride (F-). The results of the groundwater analysis revealed significant variations in physicochemical parameters across different sampling locations. The pH levels ranged from acidic to alkaline, with certain areas exhibiting values beyond the acceptable range. Elevated levels of TDS and EC were observed in specific locations, indicating potential contamination sources. The concentrations of chloride, nitrate, sulfate, and fluoride were also found to exceed the permissible limits in some areas, suggesting contamination from anthropogenic activities such as agricultural runoff, industrial discharges, and improper waste management. Furthermore, statistical analysis techniques were employed to assess the correlation between different parameters and to identify potential sources of contamination. Geographical Information System (GIS) mapping was utilized to visualize the spatial distribution of groundwater quality parameters, facilitating the identification of high-risk areas. The findings of this study provide critical insights into the current state of groundwater quality in Anantnag, Kashmir, highlighting areas that require immediate attention for remediation and management. The results can serve as a valuable reference for policymakers, water resource managers, and other stakeholders to implement appropriate measures for the protection and sustainable use of groundwater resources in the region. Additionally, this study emphasizes the importance of continuous monitoring and periodic assessments to ensure the long-term availability of safe and potable groundwater in Anantnag, Kashmir.